Management of power transactions using particle swarm optimisation - Walde P.; Singh S.P. (My University, 2025)
In this paper, a particle swarm optimisation (PSO) technique has been proposed for congestion management in different market structures comprising pool model, mix of pool and bilateral contracts by change in generation, such that the line flow which violate the limit are alleviated and the system security is maintained. The first stage describes a technique for selection of suitable participating generators using generator sensitivities to the power flow in the congested lines. An optimal power dispatch model is formulated to minimise the rescheduling of generated power in the second stage. The third stage describes the PSO technique. The solution of the above problem is obtained by PSO and GAMS (generalised algebraic modelling systems). The proposed technique has been tested on Modified IEEE-30 and the 39-bus New England systems for above mentioned market transactions. The results so obtained are promising and show the effectiveness of the proposed approach when compared with the results of GAMS and other reported methods. Thus it is demonstrated that the congestion is alleviated and the proposed method outperform the other methods. Copyright © 2012 Inderscience Enterprises Ltd.